(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Experiments were conducted to develop lightweight composites based on thermosetting polymers with cenosphere fillers. Cenospheres are rich in Al and Si particles and are known as low-density aluminosilicate CFA microspheres. The production of a polymer-based structural material (composite) with reduced weight and good mechanical properties, in which a waste product polluting the environment is used as a filler, is a current engineering task. Epoxy, polyester and vinylester resins were used, as well as different filler concentrations (cenospheres – 5 wt.%, 10 wt.% and 15 wt.%). The mechanical properties of the developed composites were studied. It was found that the use of cenospheres positively affects the mechanical properties of the vinylester resin, while in the case of other thermosetting plastics an increase in some of the mechanical characteristics was registered.